Seen this scene? Scene recognition in the reaction-time Concealed Information Test. - Norman, Danielle G.; Gunnell, Daniel A.; Mrowiec, Aleksandra J.; Watson, Derrick G. (Memory & Cognition, 2020)
Detecting a suspect's recognition of a crime scene (e.g., a burgled room or a location visited for criminal activity) can be of great value during criminal investigations. Although it is established that the Reaction-Time Concealed Information Test (RT-CIT) can determine whether a suspect recognizes crime-related objects, no research has tested whether this capability extends to the recognition of scenes. In Experiment 1, participants were given an autobiographic scene-based RT-CIT. In Experiment 2, participants watched a mock crime video before completing an RT-CIT that included both scenes and objects. In Experiment 3, participants completed an autobiographic scene-based RT-CIT, with half instructed to perform a physical countermeasure. Overall, the findings showed that an equivalent RT-CIT effect can be found with both scene and object stimuli and that RT-CITs may not be susceptible to physical countermeasure strategies, thereby increasing its real-world applicability.